2020
DOI: 10.1111/bjh.17014
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir during induction chemotherapy for newly diagnosed paediatric acute lymphoblastic leukaemia with concomitant SARS‐CoV‐2 infection

Abstract: The COVID‐19 pandemic potentially makes treatment of acute leukaemia more difficult. Most induction chemotherapy regimens for acute leukaemia lead to extended periods of cytopaenia and immunosuppression rendering patients vulnerable to opportunistic infections. As with many aspects of SARS‐CoV‐2, there is no universally accepted way of treating patients who present with acute leukaemia and associated infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 12 publications
0
32
1
Order By: Relevance
“…In 29 studies ( n = 177 patients), 8,11–14,16–39 there was a mention of the type of test used to detect SARS‐CoV‐2. Among the 177 patients in these studies, PCR‐based tests were used to establish the diagnosis in 142 (one was also positive on CBNAAT) and antibody‐based tests in 23 (the type of test used was not mentioned for 12 patients in the study by Montoya et al 18 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 29 studies ( n = 177 patients), 8,11–14,16–39 there was a mention of the type of test used to detect SARS‐CoV‐2. Among the 177 patients in these studies, PCR‐based tests were used to establish the diagnosis in 142 (one was also positive on CBNAAT) and antibody‐based tests in 23 (the type of test used was not mentioned for 12 patients in the study by Montoya et al 18 …”
Section: Resultsmentioning
confidence: 99%
“…In 196 patients (31 studies), 5,10–39 there was a mention about the type of malignancy, and 120 (53%) had hematological malignancies, and 76 (47%) had solid tumors. In studies that reported remission status (18 studies), 23 patients out of 47 were in remission from the underlying malignancy 10,11,14,20–26,29–37 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In a 5-year-old child who received remdesivir during induction chemotherapy for newly diagnosed pediatric acute lymphoblastic leukemia with concomitant SARS-CoV-2 infection, remdesivir was well tolerated with no adverse effects, except for the expected increase in ALT secondary to induction chemotherapy. 7 Just in case, using the Child-Pugh score (total bilirubin, albumin, INR, and the presence of ascites and encephalopathy) and pediatric end-stage liver disease (PELD) score (age, bilirubin, albumin, INR, and history of growth failure) for dose adjustment in COVID-19 patients with hepatic impairment should be considered by clinicians. On the other hand, according to a case series, a total of seven doses of remdesivir, which were well tolerated by stable creatinine and liver function tests throughout therapy, were successfully administered to a 19-day-old full-term infant.…”
mentioning
confidence: 99%